Asesmen Nasional Kurikulum Merdeka Belajar di Sekolah Menengah Atas (SMA) - Ahmad Mubarok; Vio Amandini Afriliana; Wahyu Azam Nur; Deby Luriawati Naryatmojo; Wagiran Wagiran (FKIP, Universitas Palangka Raya, 2025)
Assessment refers to a systematic procedure aimed at gathering information pertaining to the progress and growth of students. The implementation of assessment inside the autonomous learning curriculum aims to enhance the existing evaluation system, which now emphasizes student proficiency only in the cognitive domain. The issue at hand has posed a significant challenge within the realm of education, particularly at the secondary school level. This study employs a literature review methodology to gather scientific data and information pertaining to pertinent ideas, methodologies, and approaches found in academic journals and publications that are focused on national assessments within the context of the autonomous learning curriculum at the secondary education level. According to the findings of the study, it has been determined that genuine assessment is a suitable kind of evaluation for high school students. This type of assessment encompasses the cognitive, emotional, and psychomotor domains. In addition to this, considering the inherent characteristics and structure of real assessment, students acquire enhanced proficiency and capability, so equipping them for successful transition into the workforce or further educational pursuits.